Adaptation of the Root System to the Environment - Montagnoli, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a collection of fundamental and applied research on the plant root response to environmental clues. In particular, the continued adaptation of both fine and coarse roots to modifications due to natural and anthropogenic causes were investigated from different viewpoints. Additionally, specific root traits were investigated as an optimal indicator of responses to the environment at the whole-plant level. Aspects such as an innovative methodological approach, the root morphology, gene expression, and primary and secondary metabolite concentrations were at the center of the investigations conducted in this collection.